Appropriate Antitrust Policy Towards Single-Firm Conduct - Dennis W. Carlton; Ken Heyer (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
In this article we distinguish between two types of single-firm conduct. The first, which we call "extraction," is conduct engaged in by the firm to capture surplus from what the firm has itself created independent of the conduct's effect on rivals. The second, which we call "extension," is single firm conduct that increases the firm's profit by weakening or eliminating the competitive constraints provided by products of rivals. We propose as a fundamental antitrust policy towards single-firm conduct the following: Conduct merely to extract surplus the firm has created independent of the conduct's effect on rivals should be permitted. Conversely, conduct that extends the firm's market power by impairing the competitive constraints imposed by rivals presents a legitimate cause for concern. We subscribe strongly to the view that an essential element of appropriate antitrust policy is to allow a firm to capture as much of the surplus that, by its own investment, innovation, industry or foresight, the firm has itself brought into existence. We believe that alternative approaches to single-firm conduct, including in particular ones aiming to enhance static efficiency at the possible cost of dynamic efficiency and ones seeking to maximize overall welfare through more targeted intervention on a case-by-case basis (not to mention the use of competition policy to protect competitors rather than consumers) threaten seriously to impede economic growth and welfare over time. A policy that goes further, and which permits all unilateral conduct regardless of competitive effects (perhaps on grounds that "even more profit will generate even more innovation") is considered below and rejected as overly lenient, inconsistent with widely accepted presumptions in favor of inter-firm competition, and unwise, at least under the current state of economic knowledge. But we note that this conclusion is one based on our current economic knowledge and should remain a topic of ongoing research. It requires an empirical assessment of the gains from motivating more competition ex ante versus the subsequent loss of competition ex post.
Keywords: L41; L42; K21; 330; Competition; Single-Firm Conduct; Monopolization; Antitrust